High evening salivary cortisol is an independent predictor of increased mortality risk in patients with systolic heart failure. (15th January 2016) - Hammer, Fabian; Deutschbein, Timo; Marx, Almuth; Güder, Gülmisal; Michalski, Roman; Ertl, Georg; Allolio, Bruno; Angermann, Christiane E.; Störk, Stefan; Fassnacht, Martin
Abstract: Aims: Serum cortisol independently predicts mortality risk in patients with systolic heart failure. Salivary cortisol may provide advantages as it better reflects the biologically active free compound. Furthermore, sampling is non-invasive and may easily be performed in outpatients. We comparatively evaluated associations of morning (MSC) vs. evening salivary cortisol (ESC) and all-cause mortality risk. Methods and results: MSC (8 am) and ESC (9 pm) were determined in 229 patients with heart failure participating in the Interdisciplinary Network for Heart Failure program (66 ± 13 years; 21% female; 37% New York Heart Association (NYHA) class III/IV, median left ventricular ejection fraction 33%). The association of cortisol with mortality risk was determined by univariate and Cox multivariable regression analyses adjusting for age, sex, NYHA class, and N-terminal pro-hormone B-type natriuretic peptide. Compared to ESC, MSC was significantly higher and exhibited a higher variance: median 0.59 ng/ml (interquartile range 0.41–0.93) vs. 0.25 ng/ml (0.15–0.48), p < 0.001. During 18 months of follow-up, 25 (11%) patients died. In univariate and multivariable models mortality risk was not increased in the highest MSC quartile: crude hazard ratio (HR) 1.81 (95% confidence interval 0.79–4.14, p = 0.160), adjusted HR 1.26 (0.51–3.13, p = 0.616). However, patients in the highest ESC quartile had a significantly increased mortality risk, suggesting that associations of high ESC and increased mortality were independent of disease severity: crude HR 3.33 (1.50–7.42, p = 0.003), adjusted HR 2.49 (1.01–6.14, p = 0.047). ESC alone proved the best predictor of mortality. Conclusion: High ESC but not MSC levels independently predict increased mortality risk in heart failure.